Soil Water Dynamics in Apple Orchards of Different Ages on the Loess Plateau of China - Wang, D. (2020)
We monitored soil water content (SWC, measured using a neutron probe) and calculated soil water storage (SWS), available SWS (ASWS), and soil desiccation along 0‐ to 600‐cm soil profiles in both orchards from May to September in 2012, 2013, 2014, and 2015. For both orchards, annual mean SWCs along the 0‐ to 600‐cm profile differed during the past 4 yr. Mean SWC along the profile was consistently higher in the 7‐yr‐old orchard at both monthly and annual timescales. Accordingly, monthly mean SWS and ASWS along the 0‐ to 600‐cm soil profiles were consistently lower in the 17‐yr‐old orchard. Moreover, a dried soil layer (DSL) had formed in the soil of the 17‐yr‐old orchard and there was slightly desiccation in the 320‐ to 600‐cm layers, but no DSL was detected in the 7‐yr‐old orchard during the four study years. Tree age was mostly responsible for the differences in soil water dynamics in apple orchards. Therefore, it is important to take tree age into account when considering soil water management regimes in orchards in both the focal region of the Loess Plateau and other water‐limited regions around the world.